Productive and Reproductive Efficiency of Red Chittagong Cattle Under Farm Condition (Progressive Agriculture, 2014)
The productive and reproductive efficiency of Red Chittagong cattle (RCC) reared at the Bangladesh Livestock Research Institute (BLRI) farm was evaluated. A total of 46 RCC of different categories were considered under this study. Parameters studied were birth weight, weight at 3, 6 months of age and adult body weight, growth rate, daily milk yield, lactation length, lactation yield, age at puberty, weight at puberty, age at first calving, post partum estrus period, service per conception, calving interval and gestation length of RCC were collected and recorded. The birth weight differed significantly (p